Impact of Frozen Storage Period (-18±1°C) and Formulation on Keeping Quality of Vacuum Packaged Functional Chicken Sausages - Indumathi, Janagam (International Journal of Bio-resource and Stress Management, 2026)
The present research was carried out during 2024 (June to December, 2024) in the Department of Livestock Products Technology, College of Veterinary Science, Sri Venkateswara Veterinary University, Tirupati, Andhra Pradesh, India to determine the shelf-life of vacuum packaged functional chicken sausages and its organoleptic qualities was carried out with the objectives to assess the storage stability and sensory qualities of spent chicken sausages stored at frozen (-18°C) temperature. Functional chicken sausages were developed with 10% level of replacement of chicken fat with grounded poppy, sesame, groundnut seeds and were analysed for their keeping quality along with high fat control kept at frozen (-18±1°C) temperatures for 180 days. Results revealed that, there was significant (p<0.05) effect on functional chicken sausages with replacement of fat with 10% level of ground vegetable oil seeds under frozen storage. FFA, TBARS, tyrosine, pH and all microbiological parameters of chicken sausages were significantly (p<0.05) influenced by formulation in frozen storage and functional chicken sausages were found to have significantly lower values than control. Regardless of formulation, the mean values of pH, FFA, TBARS, tyrosine, standard plate, psychrophilic, yeast and moulds, lactobacillus and anaerobic counts were significantly (p<0.05) increased throughout the storage period in all chicken sausages under frozen conditions. Scores for all sensory attributes decreased significantly (p<0.05) in all chicken sausages irrespective of formulation. Combination of vacuum packing and fat replacement with ground vegetable oilseeds reduced lipid oxidation and microbial growth in chicken sausages and maintained the sensory quality characteristics during frozen storage for 180 days.